2000
DOI: 10.1097/00005537-200001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Glomus Jugulare Tumors

Abstract: Objectives/Hypothesis: Surgery is considered to be the mainstay of treatment for glomus jugulare tumors. A subset of patients are poor surgical candidates based on age, medical problems, tumor size, or prior treatment failure. The purpose of this study was to review our results with stereotactic radiosurgery (gamma knife treatment) in this group of patients, with particular attention to adverse reactions and symptom relief. Study Design: Retrospective review and phone survey. Methods: Charts were reviewed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 12 publications
6
71
0
1
Order By: Relevance
“…Reported complications include radionecrosis of bone, possible induction of secondary malignancies, and xerostomia. 13,14 The introduction of intensity-modulated radiation therapy has reduced the amount of normal tissue exposed to radiation, to avoid the side effects. Despite these drawbacks, the introduction of radiosurgery has offered a new technique to deliver radiation precisely.…”
Section: Neurosurg Focus / Volume 17 / August 2004mentioning
confidence: 99%
“…Reported complications include radionecrosis of bone, possible induction of secondary malignancies, and xerostomia. 13,14 The introduction of intensity-modulated radiation therapy has reduced the amount of normal tissue exposed to radiation, to avoid the side effects. Despite these drawbacks, the introduction of radiosurgery has offered a new technique to deliver radiation precisely.…”
Section: Neurosurg Focus / Volume 17 / August 2004mentioning
confidence: 99%
“…Jordan et al 17 included 8 patients; 1 worsened clinically, although all tumors were controlled and all of the other patients were stable clinically or improved. In Pollock's study, 35 nearly all of the 37 tumors analyzed were controlled, including 12 lesions that regressed.…”
Section: Radiosurgical Treatmentmentioning
confidence: 99%
“…This is in part due to the radioresistant nature of cranial nerves. 5 However, among affected patients, reported side effects include transient lower cranial nerve neuropathy, 17,37 transient nerve palsy, 9 and trigeminal neuralgia. 40 Although stereotactic radiosurgery has lower rates of morbidity than surgery or conventional whole-brain radiation therapy, some investigators have proposed that fractionated stereotactic radiosurgery would further reduce the risk of cranial nerve toxicity when treating brain tumors with radiosurgery.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11]17,18 Foote and colleagures 8,9 reported their experience with GKS in 9 patients with glomus tumors and demonstrated tumor control with no long-term complications. Jordan et al 10 reported no tumor progression and no delayed cranial neuropathies in their series of 8 patients treated with GKS. The longest follow-up has been reported more recently by Bari et al, 1 who treated 8 patients with glomus jugulare tumors by using GKS, with a follow-up range of 52-97 months.…”
Section: Gamma Knife Surgerymentioning
confidence: 99%
“…Patients can also present with cranial nerve deficits of the 9th, 10th, and 11th cranial nerves secondary to the mass effect on neighboring structures such as cranial nerves and vasculature. 10 Others present with thrombus of the nearby venous structures, whereas a small percentage of patients initially present with labile blood pressures and tachycardia secondary to catecholamine release by the tumor.…”
mentioning
confidence: 99%